Preemptive reduction of immunosuppression upon high urinary polyomavirus loads improves patient survival without affecting kidney graft function. Issue 6 (20th October 2016) - Broeders, Emine Nilufer; Hamade, Anwar; El Mountahi, Fadoua; Racapé, Judith; Hougardy, Jean‐Michel; Le Moine, Alain; Vereerstraeten, Pierre
Abstract: Background: Polyomavirus (PV) is a major cause of kidney graft disease. Monitoring by polymerase chain reaction (PCR) on blood is currently recommended. In order to avoid irreversible lesions, we investigated the clinical impact of preemptive reduction of immunosuppression (IS) in kidney transplant recipients (KTR) upon detection of high urinary PV (Upv) load, including BK virus and JC virus. Material and methods: From 2000 to 2011, in our single center, 789 consecutive KTR were distributed into 4 groups, according to the maximal Upv levels (by PCR) during the first year and the therapeutic option: (A) Upv <10 4 copies (cp)/mL ( n =573), (B) ≥10 4 Upv <10 7 cp/mL ( n =100), and (C) Upv ≥10 7 cp/mL ( n =116); in group C, the IS drug doses were reduced in subgroup Ca ( n =102) only, as 14 patients (subgroup Cb) were at risk for graft rejection. Results: The preemptive reduction of IS (group Ca) increased patient survival as compared with all other groups ( P <.05), did not modify graft function, and increased graft survival vs group A (risk ratio: 5.7, confidence interval: 1.8–18.1, P =.003). Differences for risk factors are as follows (groups Ca vs A): incidence of human leukocyte antigen (HLA) immunization (>5% panel reactive antibodies): 3% vs 8% ( P =.05), number of HLA mismatches: 2.7 vs 2.5 ( P =.049), and incidence of acute rejection: 9.8% vs 24.2% ( P =.005). PV‐associated nephropathy occurred only in group Ca (2% of total grafts) without effect on patient or graft outcome. Conclusion: The reduction of IS in patients with high Upv loads is beneficial for patient survival and does not affect graft survival or graft function.